2017
DOI: 10.3389/fmicb.2017.00686
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins Producing Endophytic Fungus Porostereum spadiceum AGH786 Rescues Growth of Salt Affected Soybean

Abstract: In the pursuit of sustainable agriculture through environment and human health friendly practices, we evaluated the potential of a novel gibberellins (GAs) producing basidiomycetous endophytic fungus Porostereum spadiceum AGH786, for alleviating salt stress and promoting health benefits of soybean. Soybean seedlings exposed to different levels of NaCl stress (70 and 140 mM) under greenhouse conditions, were inoculated with the AGH786 strain. Levels of phytohormones including GAs, JA and ABA, and isoflavones we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
101
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(112 citation statements)
references
References 69 publications
(92 reference statements)
11
101
0
Order By: Relevance
“…Production of phytohormones is a key attribute enabling endophytes to promote plant growth by improving the ability of the host to tolerate and overcome different abiotic and biotic environmental stresses (Ma et al 2016;Hamayun et al 2017;Khan et al 2017;Sandhya et al 2017). Therefore, to determine the phytohormones i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of phytohormones is a key attribute enabling endophytes to promote plant growth by improving the ability of the host to tolerate and overcome different abiotic and biotic environmental stresses (Ma et al 2016;Hamayun et al 2017;Khan et al 2017;Sandhya et al 2017). Therefore, to determine the phytohormones i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, concentration of GAs and IAA varied in the culture of the same fungus grown on various nutrients and pH (Waqas et al 2014). Furthermore, production of GA by various endophytic fungi has been reported as the most significant characteristic of PGPF (Zhang et al 2016;Hamayun et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Penicillium funiculosum, Aspergillus fumigatus sp. LH02 (Khan et al 2011), Porostereum spadiceum AGH786 (Hamayun et al 2017), and Aspergillus clavatus Y2H0002 (You et al 2015) have been recently revealed to produce various kinds of gibberellins in their growth cultures. The current study suggests the existence of gibberellin biosynthesis where the end-product is GA 4 not GA 3 in Preussia sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, endophytes such as Porostereum spadicium have been shown to produce GAs that enhanced the ability of soybean to tolerate salt stress. 73 Similarly, soybean roots inoculated with a specic strain of Aspergillus fumigatus exhibited increased shoot length, increased shoot and leaf biomass, and photosynthetic rates under salt stress compared to noninoculated plants. 74 Exhaustive reviews on the history of gibberellin research, its biological mechanisms, and the ability of plant-associated microbes to produce GAs were published recently by Hedden and Sponsel, 72 and Khan et al 75 There is however only limited knowledge on GA biosynthesis in plantassociated bacteria.…”
Section: Microbial Phytohormonesmentioning
confidence: 96%